Chemical Analysis of Dairy Products - Singh, S.K. (New Delhi: Oxford Book Co., 2016)
Any dairy product is a variable mixture of a large number of different chemical species. For compositional analysis, these chemical species are usually grouped together into broad classes such as water, fat, protein, lactose and minerals.Dairy Products
Includes Bibliography references and index material.
Keywords: Dairy Products; Analysis